Progression-free survival versus post-progression survival and overall survival in WHO grade 2 gliomas - Lisa Millgård Sagberg; Øyvind Salvesen; Asgeir Store Jakola; Erik Thurin; Eddie de Dios; Noah L.A. Nawabi; John L. Kilgallon; Joshua D. Bernstock; Vasileios K. Kavouridis; Timothy R. Smith; Ole Solheim (Acta Oncologica)
Background and purpose: Progression-free survival (PFS) remains to be validated as an outcome measure for diffuse WHO grade 2 gliomas, and knowledge about the relationships between PFS, post-progression survival (PPS), and overall survival (OS) in this subset of tumors is limited. We sought to assess correlations between PFS and OS, and identify factors associated with PFS, PPS, and OS in patients treated for diffuse supratentorial WHO grade 2 gliomas.